2020
DOI: 10.1057/s41599-020-0530-4
|View full text |Cite
|
Sign up to set email alerts
|

Developing social and civic competence in secondary education through the implementation and evaluation of teaching units and educational environments

Abstract: Recent international research in social science teaching highlights difficulties adolescents face when constructing social and citizenship awareness, and their own identity. To shed more light on this process, the present study is framed in the context of social science classrooms, and more specifically around how social and civic competence is developed via particular teaching methodologies and specific learning environments in Spain. The focus is on the analysis of democratic citizenship, as it is commonly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…For Hess (2009), controversy, debate, and discussion are the most powerful strategies with which to generate an education for an aware citizenship. The research study of Fuentes-Moreno et al (2020) corroborates these ideas. Based on the design and implementation of five didactic units with the common denominator of working on social problems for the development of civic competence, those authors used teaching methods based on a challenge or question, analysis of sources, and applying the hypothetical-deductive method.…”
Section: School Inquiry Processes As a Strategy For The Construction Of Global Citizenship Among Pupilssupporting
confidence: 77%
See 1 more Smart Citation
“…For Hess (2009), controversy, debate, and discussion are the most powerful strategies with which to generate an education for an aware citizenship. The research study of Fuentes-Moreno et al (2020) corroborates these ideas. Based on the design and implementation of five didactic units with the common denominator of working on social problems for the development of civic competence, those authors used teaching methods based on a challenge or question, analysis of sources, and applying the hypothetical-deductive method.…”
Section: School Inquiry Processes As a Strategy For The Construction Of Global Citizenship Among Pupilssupporting
confidence: 77%
“…There is no room for doubt that the teacher is vital to generating rich and meaningful historical experiences for their pupils by making them aware of the sources and of the diversity of historical perspectives (Meneses et al 2019). Similarly, for teachers to be able to put into practice those historical experiences which foster citizenship among their pupils, it is vital that they develop these competencies in themselves (Tichnor-Wagner et al 2016). Fuentes-Moreno et al (2020 concluded that teachers fulfil a fundamental role in the promotion of citizenship education in their classes through the teaching of social sciences, since their role is fundamental in the choice of both content and work methods, as well as in generating learning environments that favor participatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Estepa and Travé (2012), in the case of teachers in initial training for primary education, examined how working with the research area of current and historical societies, under criteria similar to those set out in the HETEIC project 1 , greatly contributes to professional development and didactic and social transformation, as well as improvement of the school environment. Fuentes et al (2020), presented a study in which they verified the relevance of working with active, dynamic, and participatory methodologies in the initial training of teachers, with a review of the key contents under study, to promote change in the teachinglearning processes, aimed at education for democratic citizenship. This necessary preparation of future teachers for civic and democratic training has been evidenced in various works, among which we can cite those of Darling-Hammond and Bransford (2005), Leenders et al (2008), Hauver (2010), Molina et al (2013), Poce et al (2018).…”
mentioning
confidence: 99%
“…However, these mostly rely on generic didactic examples instead of responding to cultural or local diversity. A sense of belonging and knowledge of the local area can contribute to acquiring social and civic competences and forming critical citizenship [46,47]. Furthermore, local heritage is also seen as a fundamental pillar in developing historical thinking.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%